In vitro screening of sorghum parental lines for digestibility as a step toward development of superior sorghum hybrids for cattle feeding - Nasiu, Firman (My University, 2024)
Fifty-one cultivars of sorghum parental lines were used in a series of in vitro assays to assess fermentation by mixed ruminal microorganisms as a step toward the development of superior sorghum hybrids. Sorghum grains were milled to pass a 1-mm screen of a cyclone mill, and subsequently incubated for 30 hours with a mixture of artificial saliva and strained ruminal contents from fistulated cattle. The study was designed as an incomplete randomized block design due to the large number of sorghum cultivars tested. Maximum cumulative gas production (K) and time required to reach half the maximum gas production were different (P<0.01) across sorghum cultivars. Similarly, terminal pH of cultures and in vitro dry matter disappearance (IVDMD) were also different among sorghum parental lines (P<0.01). Production of volatile fatty acids (VFA) also was assessed, and substantial differences among cultivars were noted for concentrations of propionate, iso-butyrate, isovalerate, valerate, and acetate:propionate ratio (P<0.01), but no differences were observed for concentrations of acetate, butyrate, and total VFA production (P>0.05). Furthermore, forty-eight sorghum cultivars of the parental lines from in vitro experiment were investigated to measure the gelatinization temperatures using differential scanning calorimetry (DSC). Results showed that onset temperature (To) ranged from 67.54 to 83.90⁰C, peak temperature (Tp) ranged from 74.94 to 98.35⁰C, and conclusion temperature (Tc) ranged from 74.53 to 105.32⁰C. In addition, gelatinization enthalpies ([Delta]Hgel) were ranged from 1.06 to 6.49 J/g. Lower peak temperature and gelatinization enthalpies could indicate higher digestibility of sorghum grain tested. Variations in results demonstrated from both in vitro assay and DSC analysis suggest there is potential for development of sorghum cultivars that are more suitable than current cultivars as feeds for ruminants.
Keywords: Sorghum; In vitro; Gas production; Gelatinization